(3GdeTha GdeYde aj JQJjH GdEUdGM Ydi MQha GdeYLes - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3GHf GdScjJ , jYbhH Hf GSMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3GdMeO dg Ydi eG hgH dfG ef GdaWf , MeOkG jbhe HTcQc eG XgQ ef fYeI heG HWF cJGH GdgeRI (B: (3HGH GdgeRI hGdHGA (B: (3G H R s
(3BNQgG (B:s
(3i d R L M i R f O L i d e d e s
(3PcQ ajg Cf GdYQHjI aQV Ydi GdcaGjI ef ChSW cJHgG cJGH EUdGM GdefWb dGHf GdScjJ EdG Cfg eY ZRGQI Ydeg eJhYQ GdeSdc aQCi Cf jLeY Ted ThGQOg aQJHg Ydi MQha GdeYLe hRGOg CTjGA ef EjVGM NGajI hJSejI TGYQ hEJeGe HjJ hPcQ eVGYa cd MQa ai Chd HGHg hBNQ GdeWGHb hGs
(3JHUQI GdYfhGf (B:s
(3TQM hGNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B228 s
Keywords: (3GddZIs